Virulence and genetics at the molecular level of an indigenous strain of Beauveria bassiana affected by artificial and mass production media usage for sustainable insect control - Kawpet, R.; De Bels, M.; Saengyot, S. (International Journal of Agricultural Technology, 2019)
Molecular biology of indigenous strain of entomopathogenic fungus, Beauveria bassiana (Balsamo) Vuillenim (Ascomycota: Hypocreales) (strain Bbs01) based on DNA fingerprinting and enzymatic studies and based on respective RAPD-PCR and acrylamide gel electrophoresis were conducted. The results showed that neither artificial media (PDA, SDA, SDAY, MEA, NA and WA) nor mass production material (cooked rice, paddy, millet and dog feed) effect the fungal genetic stability and protease enzyme activity. Correlation analysis indicated that pathogenicity of Bbs01 to cabbage aphids, Lipaphis erysimi (Hemiptera: Aphididae) and flea beetle, Phyllotreta sinuata (Coleoptera: Chrysomelidae) were increased with protease activity. Accordingly, the most suitable respective artificial and culture material for B. bassiana Bbs01were SDAY and dog food.